Esophageal Electrical Cardioversion of Atrial Fibrillation: When Esophagus Gives a Help to Cardiologists - Luca Santini; Giovanni B. Forleo; Francesco Romeo (Cardiology Research and Practice)
Atrial fibrillation is a common clinical disease especially in the elderly and in patients with organic heart disease. Electrical cardioversion is the first choice therapeutic approach for patients in which sinus rhythm could improve the quality of life and where the maintenance of sinus rhythm is considered likely. There are different techniques to perform an electrical cardioversion, each with specific indications, advantages, and limitations. The method most frequently used to restore sinus rhythm is external direct current cardioversion; however, this technique has some disadvantages, since it requires a high energy and usually general anesthesia. Esophageal cardioversion is an alternative method to obtain restoration of sinus rhythm, warranting acute and long-term results absolutely comparable with those obtained by the conventional transthoracic technique, especially in obese and COPD patients with high thoracic impedance for whom the standard technique may be less effective.